(untitled) (Fiep Bulletin - online, 2012)
The purpose of the study is to analyze artistic productions, specifically Brazilian popular music, soccer, and their political relations. We have prepared classifications following by the Análise do Discurso (Discourse Analysis) method, according to Orlandi (1999), identifying national political, social and cultural categories existing in the lyrics of songs/music. The study revealed that among artistic popular music by using soccer expresses the social and political conditions of the time when it was composed.